Sublobar resection for non-small cell lung cancer: a narrative review of recent new investigations - Scott, Benjamin; Duggan, John; Swanson, Scott J. (Video-Assisted Thoracic Surgery; Vol 11 (June 30, 2026): Video-Assisted Thoracic Surgery, 2026)
New research supporting sublobar resection for non-small cell lung cancer (NSCLC) has become more prevalent over the past few years. This challenges the previous paradigm of lobectomy as the standard of care for oncologic resection and offers a less aggressive surgical treatment while preserving lung parenchyma and achieving favorable oncologic outcomes. The purpose of this review is to provide the reader with the most up-to-date evidence and clinical applications for sublobar resection in patients with early-stage NSCLC.